IMPACT OF COVID-19 ON BRAND LOYALTY IN FMCG SECTOR: IN INDIA. - Nagpal, Dr. Ankita; Pallvi, Ms. Kritika (The journal of contemporary issues in business and government, 2022)
The global impact of the Coronavirus pandemic is unprecedented, and consequently the impact is even greater in emerging economies like India. Fast-moving consumer goods (FMCG) is one of the most important sectors in India, with numerous businesses, including domestic, care, and so on, that are in high demand, regularly consumed, and services are offered for a minimal cost. This paper is a decision to investigate the COVID-19 epidemic in the FMCG sector.